2019
DOI: 10.2478/jomb-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selenium supplementation on carbohydrate metabolism and oxidative stress in pregnant women with gestational diabetes mellitus

Abstract: Summary Background In the presence of conflicting advice about the relationship between selenium-type II diabetes-oxidative stress trio, this study aimed to assess the consequences of selenium supplementation on fasting plasma glucose (FPG) level, antioxidant activities of selenodependent and non-selenodependent enzymes, and other markers of oxidative stress studied for the first time during gestational diabetes mellitus (GDM). Methods This research was carried out among 180 pregnant Algerian women, 60 of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Interventional studies in women with GDM gave controversial results: in one RCT the supplementation of 200 μg/d selenium for 6 weeks from 24 to 28 GW was able to reduce fasting plasma glucose, insulin levels and Homeostasis model assessment—insulin resistance (HOMA-IR) [ 97 ]. Another RCT showed that a supplementation of 50 µg/d of selenium for 12 weeks starting from the second trimester of pregnancy could reduce fasting plasma glucose [ 98 ]. On the contrary, another trial in which pregnant women received 100 µg/d of selenium no effect on fasting plasma glucose, 2-h post-prandial blood glucose, HbA1C, insulin level, and HOMA-IR could be observed [ 99 ].…”
Section: Gdm and Gtd: Common Risk Factors?mentioning
confidence: 99%
“…Interventional studies in women with GDM gave controversial results: in one RCT the supplementation of 200 μg/d selenium for 6 weeks from 24 to 28 GW was able to reduce fasting plasma glucose, insulin levels and Homeostasis model assessment—insulin resistance (HOMA-IR) [ 97 ]. Another RCT showed that a supplementation of 50 µg/d of selenium for 12 weeks starting from the second trimester of pregnancy could reduce fasting plasma glucose [ 98 ]. On the contrary, another trial in which pregnant women received 100 µg/d of selenium no effect on fasting plasma glucose, 2-h post-prandial blood glucose, HbA1C, insulin level, and HOMA-IR could be observed [ 99 ].…”
Section: Gdm and Gtd: Common Risk Factors?mentioning
confidence: 99%
“…The rest of parameters were oxidative stress index-OSI ( n = 3), GST ( n = 2), GR ( n = 2), uric acid ( n = 2), xanthine oxidase ( n = 2), TOS ( n = 1), TNF-α ( n = 1), IL-10 ( n = 1), paraoxonase (PON-1) ( n = 1), inactivation of aldehyde dehydrogenase ( n = 1), irisin ( n = 1), bilirubin ( n = 1), 8-OHdG ( n = 1), sulfhydryl groups ( n = 1), plasma and erythrocyte carbonyl proteins ( n = 1), heme oxygenase 1 ( n = 1), nuclear factor erythroid 2-related factor-2 ( n = 1), quinone oxidoreductase (NQO1) ( n = 1), aldo-keto reductase family 1 member c1 (AKR1C1) ( n = 1), 8-iso-prostaglandin F2α (1), ceruloplasmin (1), hs-CRP ( n = 1), transferrin ( n = 1), advanced oxidative protein products (AOPPs) ( n = 1), protein carbonyl (PCO) ( n = 1), GPx3 ( n = 1), protein (P-SH) ( n = 1), total nitrite ( n = 1), non-protein thiol (NP-SH) ( n = 1), total thiol ( n = 1), non-protein thiol (NP-SH) ( n = 1), P66Shc mRNA ( n = 1), Drp1 mRNA ( n = 1), protein ROS ( n = 1), antioxidant enzymes and gene expression for mitochondrial function: ND2, TFAM, PGC1α, and NDUFB9 ( n = 1) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study found that malondialdehyde level, another indicator of oxidative stress, is increased in cirrhotic and liver transplant patients compared to normal population. Oxidative stress was demonstrated to play a role in the development of hepatic damage in many studies [36] . Interestingly, we found our study that levels of these antioxidant enzymes were still significantly lower after liver transplantation compared to normal population.…”
Section: Discussionmentioning
confidence: 99%